Study of Seawater Intrusion in Deep Aquifers of Semarang Coast Using Natural Isotopes and Hydrochemicals - Wijatna, Agus Budi; Kayis, Muhammad; Satrio, Satrio; Pujiindiyati, Evarista Ristin (Indonesian Journal on Geoscience, 2019)
DOI: 10.17014/ijog.6.1.17-28Seawater intrusion in deep aquifers of Semarang Coast is important to be investigated, because Semarang is one of big cities in Indonesia. Besides its dense population, the growth of industries also increases rapidly with the increase of withdrawal of groundwater either from shallow or deep aquifers. Over-exploitation of groundwater can cause a decreasing groundwater quality due to seawater intrusion. Through this study, the salinization from seawater into the deep aquifer system can be observed. Groundwater samples were collected from deep aquifers with the depth around 40-120 m, and then the isotope contents of 18O and 2H as well as the hydrochemical were analyzed. The isotope and hydrochemical analysis results show that six of thirteen samples are of freshwater type. They are in S2, S5, S7, S8, S9, and S13 sites. While the others are supposed to be encroached by seawater. The slight encroached groundwater of S1, S6, and S10 had a fraction of seawater in the range of 0.15 to 0.26, whereas the moderate and high ones were of S3, S4, S11, and S12 which had seawater fraction between 0.25 and 0.34. Seemingly, salinization mechanism of groundwater by seawater does not depend on its distance from the shoreline and bore well depth. It is confirmed to the site of S5 and S7 located 680 m and 950 m from the shoreline, respectively, which were predominated as freshwater type. On the contrary, the groundwater of S10, S11, and S12 located at further sites about 5-6 km from shoreline is clearly indicated seawater intrusion.